Synthesis of 3-Oxoisoindoline-1-carboxamides through Sequential Four-Component Ugi Reaction/Oxidative Nucleophilic Substitution of Hydrogen - Amiri, Kamran; Balalaie, Saeed; Anwar, Muhammad U.; Al-Harrasi, Ahmed (Synlett, 2020)
This paper describes a diversity-oriented approach to the formation of 3-oxoisoindoline-1-carboxamide derivatives utilizing the potential of the nitro group as a directing group. The reaction proceeds through a novel class of post-transformation reactions through a sequential four-component Ugi reaction/oxidative nucleophilic substitution of hydrogen. The 3-oxoisoindoline-1-carboxamide derivatives were synthesized in the presence of a base under mild reaction conditions with high regio- and chemoselectivity. The aerobic oxidation, high bond-forming efficiency, high atom economy, and good to excellent yields are the main advantages of this approach.
Keywords: oxoisoindolinecarboxamides; Ugi reaction; multicomponent reaction; nucleophilic substitution